Cyber Diplomacy And Protection Measures Against Threats Of Information Communication Technology In Indonesia - Muhammad Ridho Iswardhana (Journal of Islamic World and Politics, 2021)
This article attempts to explain the forms of Indonesian cyber diplomacy related to the protection of the use of information technology. In this case, Indonesia as the fourth largest country in the world often gets cyber threats and attacks. This was then followed up with efforts to protect it domestically, but was constrained by threats from abroad.The research method used in this study uses a qualitative descriptive analytical approach using the theoretical framework of cyber diplomacy and the concept of information and communication technology. The case analysis will explain the causes and effects of holding Indonesian cyber diplomacy based on secondary data. The author finds that the Indonesian government does not only use a legal approach through the ITE Law, but also culture, technological renewal, and diplomacy towards various countries.